Analisis Kualitas Air Sungai Bawah Tanah Gua Ngerong, Kecamatan Rengel, Tuban - Suprayogi, Dedy; Nengse, Sulistiya; Hakim, Abdul (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2019)
Fulfillment of water quality requirements is absolutely necessary to fulfill primary human needs, especially drinking water and clean water sources, both in quantity and quality. Study of the underground caverns found the fact that in terms of quantity of water availability in the reservoir is able to meet the needs of residents of the Rengel District, but qualitatively not yet known the water quality in the reservoir. The purpose of this study was to measure the water quality of underground caves in caves which include temperature, turbidity, TDS, DO and pH. The method used in this study is a qualitative method to measure the value of water quality. The research sample was taken with three repetitions for data validity. The sampling location is the underground cave system with a length of 1 km, sample points include dark zone 1, dark zone 2, dark zone 3, and dim zone. Measurements were taken in the laboratory. The results of the study showed that the average values for temperature, turbidity, TDS, DO and pH were 26.7; 1,9; 348.2; 1,6; and 7.1. The conclusion obtained from this study is that all indicators except DOs meet environmental quality standards set by the government.